2010
DOI: 10.1021/ja908687k
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Studies of HIV-1 Capsid Protein Assemblies

Abstract: In mature HIV-1 virions, a 26.6 kDa CA protein is assembled into a characteristic cone shaped core (capsid) that encloses the RNA viral genome. The assembled capsid structure is best described by a fullerene cone model that is made up from a hexameric lattice containing a variable number of CA pentamers, thus allowing for closure of tubular or conical structures. In this report, we present a solid-state NMR analysis of the wild type HIV-1 CA protein, prepared as conical and spherical assemblies that are stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
153
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(170 citation statements)
references
References 78 publications
14
153
0
3
Order By: Relevance
“…CA (HXB2, NL4-3, NL4-3/A92E, and NL4-3/G94D variants) and CypA were expressed and purified by using the same protocol as reported (14,41). Tubular assemblies of CA protein were prepared and their morphology characterized as described (14) and detailed in SI Appendix, SI Text.…”
Section: Methodsmentioning
confidence: 99%
“…CA (HXB2, NL4-3, NL4-3/A92E, and NL4-3/G94D variants) and CypA were expressed and purified by using the same protocol as reported (14,41). Tubular assemblies of CA protein were prepared and their morphology characterized as described (14) and detailed in SI Appendix, SI Text.…”
Section: Methodsmentioning
confidence: 99%
“…The conical assemblies of U- 13 C, 15 N-Tyr-labeled C-terminal domain (CTD) of HIV-1 CA protein were prepared by controlled precipitation from 50% w/v solution of PEG-4000 at the ratio of 1:1 (v/v) with the final protein concentration of 16 mg/mL, as reported previously. 38 15 N]-Ala were packed into 3.2 mm rotors, and all spectra were recorded at MAS frequencies of 10 and 20 kHz, controlled to within ±0.005 kHz. The n.a.…”
Section: Introductionmentioning
confidence: 99%
“…Although capsids within mature HIV-1 often have an approximately conical morphology, large morphological variations have been reported (10), as well as variations in apparent closure (11). Studies of pure CA performed in vitro have also found a wide variety of morphologies for CA assemblies, including tubes with 40 -60 nm diameters (3,4,(12)(13)(14)(15), spheres with minimum diameters of 20 nm and maximum diameters exceeding 10 m (2, 13, 16), planar sheets (2), and assemblies with asymmetric morphologies resembling those within mature HIV-1 (7,13,16).…”
mentioning
confidence: 99%